2022
DOI: 10.3390/cancers14235994
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pretreatment Physical and Geriatric Parameters with Treatment Tolerance and Survival in Elderly Patients with Stage I–II Non-Small Cell Lung Cancer: An Evaluation of Usual Care Data

Abstract: In this study, the association of pretreatment physical and geriatric parameters with treatment tolerance and survival in elderly patients with stage I–II NSCLC was evaluated. Retrospective data for patients aged ≥ 70 years, diagnosed between 2016 and 2020 with stage I–II NSCLC, and who underwent surgery or stereotactic ablative radiotherapy (SABR) in a large Dutch teaching hospital were retrieved from medical records. Associations of pretreatment physical and geriatric parameters with treatment tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Voorn et al found that preoperative physical parameters in elderly lung cancer patients were associated with treatment tolerance and survival, and they recommended comprehensive physical and geriatric parameters before surgery, as well as active interventions to improve the physical status of elderly lung cancer patients prior to surgery, in order to better adapt to the surgery. 28 The preoperative pulmonary functional status can have a substantial impact on the patient's prognosis and postoperative quality of life. 29 Preoperative pulmonary function training can enhance pulmonary ventilation and reduce pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Voorn et al found that preoperative physical parameters in elderly lung cancer patients were associated with treatment tolerance and survival, and they recommended comprehensive physical and geriatric parameters before surgery, as well as active interventions to improve the physical status of elderly lung cancer patients prior to surgery, in order to better adapt to the surgery. 28 The preoperative pulmonary functional status can have a substantial impact on the patient's prognosis and postoperative quality of life. 29 Preoperative pulmonary function training can enhance pulmonary ventilation and reduce pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, in elderly patients with early lung cancer, preoperative physical function parameters are linked to treatment tolerance and survival rates, and low preoperative physical function scores are linked to a higher likelihood of unfavorable treatment outcomes. 28 It is therefore recommended that older patients review their physical function before treatment, as well as chronic illnesses, and so on, in order to make a shared decision and option. Additionally, patients may benefit from preventive intervention during therapy.…”
Section: Discussionmentioning
confidence: 99%